Cervicitis associated with papillomavirus infection: prediction and management strategy choice - Shargorodskaya A.V; Bebneva T.N (LCC «Medicine-Inform», 2019)
Cervicitis associated with papillomavirus infection: prediction and management strategy choice A.V. Shargorodskaya1, T.N. Bebneva1,2 1National Medical Research Center of Endocrinology, Moscow, Russian Federation 2Russian University of Peoples' Friendship, Moscow, Russian Federation Chronic cervicitis is diagnosed in 80% of women with cervical ectropion. Human papillomavirus (HPV) provokes cervical intraepithelial lesion and prevents normal course of cervical ectropion. High contagiousity provides the infection in 80% of cases even after single sexual act. In most patients, infection is transient, and HPV is spontaneously eliminated after 12 to 24 months. However, in 10% to 20% of women persistent infection increases the risk of severe cervical intraepithelial neoplasia which can progress to invasive cancer. The paper discusses cervix inflammation associated with papillomavirus and the role of cervical ectropion as a site of the realization of papillomavirus oncogenic potential. Indications to the medical treatment and surgical procedures for complicated ectropion are addressed. The authors analyze treatment outcomes of topical medications with glycyrrhizinic acid as monotherapy or in combination with cryodestruction. Recommendations on the management of cervical ectropion associated with papillomavirus infection in women of various ages are provided. Keywords: cervical ectropion, human papillomavirus (HPV), chronic cervicitis, neoplasia. For citation: Shargorodskaya A.V., Bebneva T.N.,Cervicitis associated with papillomavirus infection: prediction and management strategy choice. Russian Journal of Woman and Child Health. 2019;2(2):143-147.